Propuesta para redistribución en planta de la empacadora de la Finca Córdoba Bis, ubicada en la Zona Bananera-Magdalena (2023)
This research project proposes a plant redistribution design for the packing house of the Córdoba Bis farm, a company dedicated to the production and export of bananas. It consists of the diagnosis, analysis and identification of opportunities for improvement in the distribution in the current plant through a study of methods and times, and in the proposal of an improvement alternative applying the Guerchet and SLP method, in order to optimize the spaces. , increase material flow, reduce time and costs, and increase baler efficiency. The methodology is evaluated through a simulation in the FlexSim software; a program that allows you to build and run the developed model in a simulation within a 3D environment from scratch. Parameters obtained through RStudio were used in the simulation process, taking into account the improvements obtained by applying the SLP method. Finally, a scenario is proposed where the distances traveled by the operators, the spaces used and the percentages of inactivity of the operators are improved, projecting a reduction in bottlenecks, the optimization of the workforce, the reduction of the risk for the health and increased safety